Cartographie des bancs de crépidules dans le bassin de Marennes Oléron: analyse par imagerie acoustique et sondeur de sédiment - Curti, Cécile (2009)
The slipper limpet Crepidula jornicata, gastropod introduced on the North East Atlantic coasts, is considered as an invasive species, especially in shellfish fmming areas in France. Slipper Iimpet populations have been estimated in Marennes Oléron Bay since 1980. In 1995, a sidescan sonar mapping associated to a quantitative estimation of the stocks by « grab » was carried out. This study aims to update the current mapping of slipper limpet beds in the Marennes Oléron Bay using acoustic reading techniques coupled to samples. In autumn 2008, an acoustic campaign was performed through the Ifremer boat named Haliotis and sonograms obtained during the campaign were then analysed using the software CARAIBES. Acoustic images were calibrated through30 grab samples which had been geolocalized. The interpretation of the 38 km2 sampled by the sonar suggests that the slipper limpet population increased to reach 7.3 km2 Most of the C. jornica/a beds were located in the North of the bay, especially the Northem part of the «bed of Lamouroux » and in the middle of the Bay, «bed of Agnas », «Courante d'Oléron », «Mortanne-Juliar» and «Craze-Charret». In the southem part of the Bay, sonograms indicated large C. fornica/a populations while samples revealed that were only found in the «bed of Bry ». Indeed, it was found that mussel beds of Mytilus edulis, instead of C. fornicata, covered an area of 1.9 km2 in the South of the Bay. Comparison between 1995 and 2008 showed an increase of several slipper limpet beds, especially in the bed of Lamouroux and in Courante Oléron. Conversely, the C. fornicata population located near the mussel farming area in Boyardville were strongly reduced showing the positive impact of dredging of the Trézence boat, chartered by the «Conseil Général 17» in 2008. The lack of spreading of slipper limpets in the south of Marennes Oléron Bay can be explained by the hydrodynamics and the topography of the bottom in this area as both are unfavourable to latval settlement of C. fornicata. However, spatial ...